All About Physics - Hammond, Richard (London Dorling Kindersley Publishing Limited, 2015)
Richard Hammond explains All About Physics in this popular, award-winning series, from the discoveries of ancient Greece to Einstein via Galileo and Newton. Physics doesn't just happen in a lab - it happens in the kitchen, in your bath, in a car! Join a thrilling high-energy journey through time, space and beyond and find out about the physical forces that make our world what it is. Find out how science affects everything, from roller-coasters to fighter pilots. Crammed with fascinating physics facts and interactive experiments. A totally cool look at physics!
Include Color Illustration and Index
Keywords: Physics -- Physics--Experiments